NIMG-21. SEX DIFFERENCES IN EXTREME SURVIVORSHIP AMONG PRIMARY GLIOBLASTOMA PATIENTS. (5th November 2018) - Whitmire, Paula; Rickertsen, Cassandra; Hawkins-Daarud, Andrea; Carrasco, Eduardo; Lorence, Julia; De Leon, Gustavo; Curtin, Lee; Bayless, Spencer; Clark-Swanson, Kamala; Peeri, Noah; Corpuz, Christina; Paula Lewis-de Los Angeles, Christine; et al.
Abstract: Glioblastoma (GBM) is an aggressive primary brain cancer that has a median overall survival (OS) of 15 months from diagnosis. Determining which pretreatment tumor characteristics are predictive of extreme survival (EXS) (OS > 1825 days) and short-term survival (STS) (OS < 210 days) has significant clinical value. Several biological markers have been discovered that are predictive of EXS or STS, but the impact of patient sex on the predictive value of these markers has been minimally explored. In this investigation, machine learning algorithms and statistical tests were used to assess which pretreatment clinical and MR image-based volumetric and kinetic parameters were significant predictors of overall survival duration for male (n=299, including 30 EXS and 46 STS) and female (n=195, including 17 EXS and 42 STS) GBM patients. When compared to the middle survivor group (210 days < OS < 1825 days), female EXS had smaller tumor volumes and both male and female EXS had lower tumor cell proliferation rates at time of diagnosis. Independent predictors of overall survival included tumor cell diffuse invasion rate among females (hazard ratio [HR] =1.011, p < 0.001), tumor size among males (HR=1.027, p=0.044) and age among both males and females (Females: HR=1.021, p=0.006; Males: HR=1.030, p < 0.001). Despite similar distributions of the MR imaging parameters between males and females, there was a sex-specific difference in how these parameters related to outcomes, which emphasizes the importance of considering sex as a biological factor when determining patient prognosis and treatment approach.